The impact of aging on neurophysiological entrainment to a metronome. Issue 10 (3rd July 2019) - Sauvé, Sarah A.; Bolt, Emily L.W.; Fleming, David; Zendel, Benjamin Rich
Abstract : In music, entrainment to the beat allows listeners to make predictions about upcoming events. Previous work has shown that neural oscillations will entrain to the beat of the music or rhythmic stimuli. Despite the fact that aging is known to impact both auditory and cognitive processing, little is known about how aging affects neural entrainment to rhythmic stimuli. In this study, younger and older participants listened to isochronous sequences at a slower and faster rate while EEG data was recorded. Steady-state evoked potentials had amplitude peaks at the stimulus rate and its harmonics. Steady-state evoked potentials at the stimulus rate and the first harmonic was attenuated in older adults compared to younger adults. Additionally, no amplitude difference was found for the second and third harmonics in older adults, while there was a decrease in amplitude in younger adults. This age-related decline in the entrainment specificity of the brain responses to the stimulus rate, suggests that aging may decrease the ability to entrain to stimuli in the environment, and further suggests that older adults may be less able to inhibit neural entrainment that is not directly related to the incoming stimulus.